2021
DOI: 10.1126/scitranslmed.abd6299
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism and reversal of drug-induced nephrotoxicity on a chip

Abstract: The kidney plays a critical role in fluid homeostasis, glucose control, and drug excretion. Loss of kidney function due to drug-induced nephrotoxicity affects over 20% of the adult population. The kidney proximal tubule is a complex vascularized structure that is particularly vulnerable to drug-induced nephrotoxicity. Here, we introduce a model of vascularized human kidney spheroids with integrated tissue-embedded microsensors for oxygen, glucose, lactate, and glutamine, providing real-time assessment of cellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(35 citation statements)
references
References 52 publications
1
33
0
1
Order By: Relevance
“…We further demonstrated that the protective effect of canagliflozin in cisplatin-induced nephrotoxicity was related to decreased cisplatin uptake by renal tubular cells and the activation of the AKT pathway ( 74 ). In addition, Cohen et al used organ-on-chip models, vascularized human kidney spheroids with integrated tissue-embedded microsensors for oxygen, glucose, lactate, and glutamine, to achieve a dynamic assessment of cellular metabolism and verified that empagliflozin (another SGLT2 inhibitor) could block cisplatin toxicity in the kidneys by impeding glucose reabsorption ( 75 ). Despite these studies, the molecular mechanisms underlying the changes of glucose metabolism in cisplatin-induced AKI remain largely unknown.…”
Section: Regulation Of Glucose Metabolism In Kidney Diseasesmentioning
confidence: 99%
“…We further demonstrated that the protective effect of canagliflozin in cisplatin-induced nephrotoxicity was related to decreased cisplatin uptake by renal tubular cells and the activation of the AKT pathway ( 74 ). In addition, Cohen et al used organ-on-chip models, vascularized human kidney spheroids with integrated tissue-embedded microsensors for oxygen, glucose, lactate, and glutamine, to achieve a dynamic assessment of cellular metabolism and verified that empagliflozin (another SGLT2 inhibitor) could block cisplatin toxicity in the kidneys by impeding glucose reabsorption ( 75 ). Despite these studies, the molecular mechanisms underlying the changes of glucose metabolism in cisplatin-induced AKI remain largely unknown.…”
Section: Regulation Of Glucose Metabolism In Kidney Diseasesmentioning
confidence: 99%
“…The kidney is also vulnerable to injuries caused by numerous challenges such as ischemia [ 8 , 9 , 10 , 11 , 12 ], drug toxicity [ 13 , 14 , 15 , 16 , 17 , 18 , 19 ], environmental heavy metal exposure [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ], hypertension [ 28 , 29 , 30 ], immune injury [ 31 , 32 ], and diabetes [ 33 , 34 , 35 , 36 ]. In terms of environmental risk factors, human kidney disease caused by environmental pollutants and occupational-linked toxins is a major public health issue [ 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…An example of a multimodal approach is provided by a recent study that identified multiple pathways altered by cisplatin in human-derived PT cells, including the Nrf2-mediated oxidative stress response, various mitochondrial processes, and AMPK, mTOR and p53 signaling [42]. Furthermore, deployment of tissue-embedded microsensors for oxygen and various metabolites in human kidney spheroids has revealed that glucose uptake is critical to the development of lipotoxicity induced by cyclosporine and cisplatin [43].…”
Section: Cellular Mechanisms Of Drug Toxicity In the Proximal Tubulementioning
confidence: 99%